Análise Estrutural e Topológica de um análogo fenilsulfonil-dihidroquinolinona obtida por hibridação molecular - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
The composition of hybrids among sulfonamides, chalcones and quinolinones has been target of study, because these compounds show biological applications like Alzheimer and Parkinson disease treatment, against several types of cancer like lymphoma and carcinoma, furthermore they are antitumoral, antioxidant, antiinflamatory, among others properties. The structural knowledge of these compounds is of great importance, because enable the study of their physical and chemical properties. In this work is presented the characterization and structural analysis of dihydroquinolinone C29H22N2O6S (DHQ). On this purpose, the x-ray crystallography methodology was utilized to solve and refine the structure. The data collected by single crystal x-ray diffraction were solved by the direct methods through the SHELXS software and refined by the least square means through SHELXL software. The geometrical parameters and intermolecular interactions were analyzed through Mercury 3.9 software. Aiming to better understand the intermolecular interaction and supramolecular arrangement of the compound, Hirshfeld surfaces and fingerprints were used with help of CrystalExplorer17 software. Besides that, theoretical calculations of vibrational spectrum and frontier molecular orbital were performed through Density Functional Theory (DFT), with help of Gaussian09 software. The main results show that the crystal packing is stabilized by C-H⋯O non-classical, C-H⋯𝜋 and C-H⋯H-C, all weak interactions. The interactions were accounted with the help of fingerprints. The main vibrational modes were assigned when comparing the experimental and calculated data, and the differences may be attributed to the fact that calculations were made with one molecule in vacuum and experimental were made in solid state. Furthermore, the structure has electrophilic sites are around groups with O atoms.
Keywords: Difração de raios X; Dihidroquinolinona; Superfícies de Hirshfeld; X ray diffraction; Dihydroquinolinone; Hirshfeld surfaces; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::QUIMICA